Adoption intentions of aquaculture farmers of the BioDOF-Map system - Man, Norsida; Che'ya, Nik Norasma; Lokman, Eleanor Daniella (Society for Innovative Agriculture, 2024)
In Malaysia, aquaculture utilizes GIS technology to optimize the selection of sites, monitor the quality of water, manage resources, and improve production, hence assuring the implementation of sustainable and efficient aquaculture techniques. The Malaysian Department of Fisheries (DOF) has created a Web-GIS system, namely BioDOF-Map to facilitate comprehension of the fishery. Nevertheless, the use of this technology presents difficulties for farmers who are not acquainted with the execution of the system. The study examines Malaysian aquaculture farmers' adoption of GIS technology, revealing high intentions influenced by attitude, subjective norms, and perceived behavioural control, suggesting policy support for technology uptake. The study highlights the crucial role of GIS technology in optimizing Malaysian aquaculture, demonstrating strong correlations between attitudes, subjective norms, perceived control, and the intention to adopt the BioDOF-Map system using the Theory of Planned conduct (TPB). A total of 278 people were surveyed in this quantitative investigation, utilising a questionnaire. 65.8% of MAFs function as landlords. Out of the total 242 individuals engaged in production, 29.2% possess land spanning an area of 3.1 to 4 hectares, whereas 69.1% reside at a distance of 2 to 3 kilometres from their agricultural plots. Significantly, 49.6% of individuals own property that has been passed down via their family, and an additional 9.7% are involved in non-agricultural activities such as growing crops. Participants engage in either the cultivation of aquatic creatures or the commercial breeding of fish in cages. Perak has the biggest proportion, accounting for 11.15% of the total, while Pahang and Selangor have proportions of 10.07% each. Sarawak represents 9.7% of the total, while Kedah accounts for 8.27%. Both Johor and Negeri Sembilan contribute 7.91% apiece. The study shows that 50.72% of MAFs are 6-10 km from the nearest town and farm, 22.30% are less than 5 km away, 18.71% are 11-15 km away, and 8.27% are over 16 km away. The average intention to implement the BioDOF-Map system was high, with a mean of 4.55 and a standard deviation of 0.296. The correlation analysis revealed a highly significant correlation between attitude and intention to adopt (r = 0.980, p = 0.000), providing evidence for a robust link between attitude and desire to adopt. Furthermore, there was a strong positive correlation between subjective norms and intention to adopt (r = 0.325, p = 0.000). Additionally, perceived behavioural control was also strongly connected with intention to adopt (r = 0.966, p = 0.000). The Ministry of Agriculture and Food Security (KPKM) and other stakeholders have a responsibility to establish policies and programmes that promote knowledge of the system and encourage better behavioural management within it. These practical implications are aimed at enhancing the adoption and utilization of GIS technology like BioDOF-Map among Malaysian aquaculture farmers, ultimately contributing to the sustainability and productivity of the aquaculture sector in Malaysia.